Low-dose CT in clinical diagnostics. (September 2013) - Fuentes-Orrego, Jorge M; Sahani, Dushyant V
Abstract : Introduction: Computed tomography (CT) has become key for patient management due to its outstanding capabilities for detecting disease processes and assessing treatment response, which has led to expansion in CT imaging for diagnostic and image-guided therapeutic interventions. Despite these benefits, the growing use of CT has raised concerns as radiation risks associated with radiation exposure. Areas covered: The purpose of this article is to familiarize the reader with fundamental concepts of dose metrics for assessing radiation exposure and weighting radiation-associated risks. The article also discusses general approaches for reducing radiation dose while preserving diagnostic quality. The authors provide additional insight for undertaking protocol optimization, customizing scanning techniques based on the patients' clinical scenario and demographics. Supplemental strategies are postulated using more advanced post-processing techniques for achieving further dose improvements. Expert opinion: The technologic offerings of CT are integral to modern medicine and its role will continue to evolve. Although, the estimated risks from low levels of radiation of a single CT exam are uncertain, it is prudent to minimize the dose from CT by applying common sense solutions and using other simple strategies as well as exploiting technologic innovations. These efforts will enable us to take advantage of all the clinical benefits of CT while minimizing the likelihood of harm to patients.